2012
DOI: 10.1590/s1516-35982012000500028
|View full text |Cite
|
Sign up to set email alerts
|

Biological and economic performance of feedlot lambs feeding on diets with different energy densities

Abstract: -The objective of this study was to evaluate performance, carcass dressing and gross profit margin of lambs of different genotypes finished in feedlot with diets containing two levels of energy (2.40 Mcal/kg dry matter -DM or 2.90 Mcal/kg DM). Fifty-four non-castrated lambs of the following genotypes were used: Santa Inês, F1 Dorper × Santa Inês and F1 Santa Inês × undefined breed at approximately 150 d of age averaging 22.6 kg of live body weight. Lambs subjected to the diet containing 2.90 Mcal/kg DM stayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
4
9
0
2
Order By: Relevance
“…The explanation to feed conversion did not have been efficient among different genetic groups is due to the fact of the consumption of dry matter and DWG expressed in kg/day also have presented significant difference. Values similar to the reported in this study are presented by Sousa et al (2012), evaluating the biological performance of pure and breed lambs of races Santa Inês and Dorper, in confinement, found average values of 5,82g/g, 5,28g/g, and 6,39g/g, to VC of animals Santa Inês, Santa Inês x Dorper and Dorper, respectively. Therefore, the values found in the present research are considered acceptable when it is working with goat species.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The explanation to feed conversion did not have been efficient among different genetic groups is due to the fact of the consumption of dry matter and DWG expressed in kg/day also have presented significant difference. Values similar to the reported in this study are presented by Sousa et al (2012), evaluating the biological performance of pure and breed lambs of races Santa Inês and Dorper, in confinement, found average values of 5,82g/g, 5,28g/g, and 6,39g/g, to VC of animals Santa Inês, Santa Inês x Dorper and Dorper, respectively. Therefore, the values found in the present research are considered acceptable when it is working with goat species.…”
Section: Resultssupporting
confidence: 90%
“…Cartaxo et al (2013) found average values of total margin of profit of R$ 6,27/ animal to animals breed of Boer x WDRP and R$0,54/animal to WDRP, when compared with animals Anlgo Nubiano x WDRP, which had otak margin of profit of R$ 0,52/animal. According to the results found in the present study, there are the results reported by Sousa et al (2012), that evaluating the bioeconomic performance of terminated lambs in confinement, related less total margin of profit to animals breed WDRP,when compared to breed with especialized races for meat production, demonstrating that the breed with races with aptitude for meat production, as the case of the animals used in this study, Boer and Savana, increases the liquid profit, because they consume less food to reach the ideal weight for slaughter. Adopting breeds, it is possible to use the contribution of heterosis, to characteristics with economic importance, aiming to reach optimal levels of development, compatible with systems of intensive production, even in the first generation, as well as the utilization of genetic resources available in production systems.…”
Section: Resultssupporting
confidence: 83%
“…PFS and marbling were similar among the genotypes (Table 5). Finishing was greater in cross Dorper sheep (3.55), indicating that breeding with animals specialized in meat production improves fat cover scores, which was observed by Sousa et al (2012), when they studied the Santa Inês, F1 Dorper x Santa Inês, and F1 Santa Inês x MB genotypes, and reported that Dorper x Santa Inês products showed greater fat cover scores. This finding was also confirmed by Álvarez et al (2013), in a study with different sheep genotypes.…”
Section: Resultsmentioning
confidence: 81%
“…CV = coeficiente de variação; P = probabilidade. Cartaxo et al (2008) e Sousa et al (2012) avaliando o desempenho bioeconômico de cordeiros terminados em confinamento, observaram menor margem bruta de lucro para os animais mestiços SRD quando comparados com os mestiços com raça especializada para corte. Da mesma forma do presente estudo os animais mestiços com raça especializada para corte obtiveram os maiores resultados.…”
Section: Resultsunclassified